From a Reform to a Reform - Meerovich, Mark (project baikal, 2016)
The article reviews two critical stages in the history of architectural profession in the USSR, when the party and state authorities imposed change on all the key principles of architectural and townplanning design in the country: stylistic, social, financial, structural-and-technological, planning and other principles. The first stage (1929-1932) implied prohibition of the Soviet Avant-Garde architecture and transition to the so-called Stalin’s Neoclassicism and was implemented by Iosif Vissarionovich Stalin. The second stage (1954-1970s) implemented by Nikita Sergeevich Khruschev consisted in renouncing of Stalin’s Neoclassicism and a revival of modern architecture focused on the use of type designs, standardization and industrialization in the construction field.
Keywords: architectural reform; panel house building; communal dwelling; khruschevkas